2018
DOI: 10.1080/07317115.2018.1485197
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Care for LGBT Older Adults in Long-Term Care Settings: Competency, Training, and Barriers for Mental Health Providers

Abstract: LGBT-specific training and EBTs are needed. Facilities need to address stigma with residents and providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 12 publications
0
26
0
1
Order By: Relevance
“…The needs of older LGBTQ + seniors should feature in nursing undergraduate, postgraduate, and CPD education programmes including mental health facets and the need to enable and facilitate access to person‐centred assessment, treatments, and supports. Such programmes should address cultural competencies for all health professionals, including nursing staff (Orel, ; Shenkman et al, ; Smith et al, ; Wong, Suksang, & Rorvig, ). While collaborating with LGBTQ + organizations in the development of appropriate curriculum content, nurse educators can integrate topics areas including ageism, caregiving, housing rights, and the unique requirements of LGBTQ + older people as a non‐homogenous group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The needs of older LGBTQ + seniors should feature in nursing undergraduate, postgraduate, and CPD education programmes including mental health facets and the need to enable and facilitate access to person‐centred assessment, treatments, and supports. Such programmes should address cultural competencies for all health professionals, including nursing staff (Orel, ; Shenkman et al, ; Smith et al, ; Wong, Suksang, & Rorvig, ). While collaborating with LGBTQ + organizations in the development of appropriate curriculum content, nurse educators can integrate topics areas including ageism, caregiving, housing rights, and the unique requirements of LGBTQ + older people as a non‐homogenous group.…”
Section: Discussionmentioning
confidence: 99%
“…Such programmes should address cultural competencies for all health professionals, including nursing staff (Orel, 2004;Shenkman et al, 2018;Smith et al, 2019;Wong, Suksang, & Rorvig, 2018 There is a distinct lack of multi-centre and international studies and longitudinal studies to investigate mental health issues, access to care and support and service use. There is increased opportunity for nursing research that specifically identifies strategies to address loneliness and social isolation.…”
Section: Nurse Educationmentioning
confidence: 99%
“…A classe 6 abordou as RS relacionadas as discriminações sofridas pelo público LGBT. Quanto a preconceito vivenciado pelo LGBT, historicamente, esse público foi rotulado por instituições religiosas como anti-família e imoral e até 1973 os relacionamentos entre indivíduos do mesmo sexo era considerado transtorno psiquiátrico (Smith, Altman, Meeks & Hinrichs, 2019;Vries, 2015).…”
Section: Discussionunclassified
“…The second theme encompasses the education and training of providers to meet the needs of this community. While health providers in long-term care settings express interest in expanding their repertoire of evidence-based care to LGBTQ older patients, surveyed providers cited a lack of training in these evidence-based approaches, and the experience that many residents hide their sexual minority status, as barriers and challenges to this work (Smith, Altman, Meeks, & Hinrichs, 2018). Using a rich qualitative approach, another study in this issue identified several critical themes regarding health providers' lack of knowledge regarding LGBTQ older adults and suggestive of strategies by which this much-desired training could be provided (Kortes-Miller, Wilson, & Stinchcombe, 2018).…”
Section: Intersectionality Of Aging and Sexual Minority Statusmentioning
confidence: 99%